Effects of aging on the shape memory behavior of Ni-rich Ni50.3Ti29.7Hf20 single crystals. (1st April 2015) - Saghaian, S.M.; Karaca, H.E.; Tobe, H.; Souri, M.; Noebe, R.; Chumlyakov, Y.I.
Abstract: The shape memory properties of solutionized and aged Ni-rich Ni50.3 Ti29.7 Hf20 single crystals were investigated along the [0 0 1], [0 1 1] and [1 1 1] orientations in compression. The effects of crystal orientation and aging temperature on the transformation strain, thermal hysteresis and Clausius–Clapeyron (CC) relation were determined. Aging at 550 °C for 3 h introduced coherent 10–20 nm precipitates in the matrix, which substantially improved the shape memory and mechanical properties of the Ni50.3 Ti29.7 Hf20 crystals. [0 0 1]-oriented single crystals showed high dimensional stability under stress levels as high as 1500 MPa in both the solutionized and aged conditions, but with transformation strains of <2%. Thermal treatments can be used to tailor the transformation temperatures over a wide range with the martensite start temperature varying from −25 °C in the solutionized case to 123 °C by aging at 650 °C for 3 h. Compared to the solutionized condition, thermal hysteresis was reduced after aging at 550 °C/3 h, but increased with aging at 650 °C. Perfect superelasticity with recoverable strain of >4% was observed for solutionized and 550 °C/3 h aged single crystals along the [0 1 1] and [1 1 1] orientations, and general superelastic behavior was observed over a wide temperature range. In contrast, aged [0 0 1]-oriented single crystals have a very high CC slope, in the range of 30–40 MPa °C −1, which results in a lack of superelasticity. Theoretical transformation strains were calculated by using the energy minimization method and lattice deformation theory. The calculated transformation strains were higher than the experimentally observed strains since the calculated strains could not capture the formation of martensite plates with (0 0 1) compound twins.